Building a Resilient and Sustainable Agriculture in Sub-Saharan Africa - Shimeles, Abebe; Verdier-Chouchane, Audrey; Boly, Amadou (Springer Nature, 2018)
Sustainable agriculture in Sub-Saharan Africa; Agricultural economics; Climate change economics; Agricultural productivity; Modern technology adoption by farmers; Agricultural sustainability; Bioenergy Crop Adoption; Agro-Industrialization; Agriculture sector development; Environmental Efficiency; Global Value Chains; Regional value chains; African economic development; African agricultural transformation; Labour productivity; Drought Index Insurance; Supplemental irrigation; Special Economic Zones; ECOWAS countries